Decolonial AestheSis Parcours - Khan, Sharlene; Asfour, Fouad (Arts Research Africa (ARA), 2020)
The Decolonial AestheSis Parcours is made up of exercises informed not only by recent theories around decolonial aestheSis, but by Black and African Feminist creativities, Critical Race Theories, postcolonial histories, liberal arts pedagogies, and anti-hegemonial cultural movements. The workshop invites participants to reflect on non-hierarchical relationships, embodied knowledges, creative theorisation, the African Feminist concept of theorising from the epicentres of our agency, the use of imagination as a tool of freedom and experimentation, the need for interrogation of capitalist modes of artistic production, interconnectivities, as well as the need for critical pleasure.
Arts Research Africa Conference Proceeding 2020
Keywords: Artistic research; Arts research; Arts research; Decolonisation; Arts pedagogy